Purification of the human G protein-coupled receptor adenosine A(2a)R in a stable and functional form expressed in Pichia pastoris. - Singh,S; Zhang,M; Bertheleme,N; Strange,PG; Byrne,B (Curr Protoc Protein Sci, 2012)
The isolation of membrane proteins with the aim of producing highly pure, homogeneous, stable, and functional material remains challenging, and it is often necessary to develop protein-specific purification protocols by trial and error. One key tool that is required in the development of a suitable protocol is a functional assay. This unit describes a range of different protocols for isolation of the human adenosine A2a receptor (A(2a)R). These protocols show the importance of developing a robust method for comparing the quality of protein obtained by a combination of biophysical analyses including SDS-PAGE, analytical size-exclusion chromatography, and functional analysis. One of the keys to isolating and maintaining a functional receptor, found not only in the optimal protocol described here but in other published examples, is that there should be no more than two chromatographic steps.